ASSESSING THE PERFORMANCE OF ISLAMIC BANKING IN BRUNEI DARUSSALAM: EVIDENCE FROM 2011-2016 - Abduh, Muhamad (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2018)
Despite being among the earliest country offering Islamic banking to its people, academics know little about the performance of the industry in Brunei Darussalam. This study is aimed at fulfilling the gap by examining the performance of Islamic banking in Brunei Darussalam after 25 years of its establishment. However, due to limited availability and nonuniformity of the data presentation, the analysis is focused upon the period of 2011 to 2016. The data are collected from secondary sources such as banks’ annual reports and central bank’s quarterly reports for the period examined. The bank idiosyncratic factors i.e. size, capital ratio, credit risk, liquidity risk, service diversification, and bank stability are the cynosure of the analysis. Descriptive statistics, Herfindahl-Hirschman Index and z-score analysis are utilized as the tool of analysis. To make it more interesting, the performance comparison is done between Islamic bank and the banking industry. The result shows that evaluated idiosyncratic factors are indicating a better performance of Islamic banking as compared to its conventional counterpart and the overall banking industry in the country.